2018
DOI: 10.1111/desc.12719
|View full text |Cite
|
Sign up to set email alerts
|

School climate is associated with cortical thickness and executive function in children and adolescents

Abstract: A positive school climate has been found to support mental and physical health, academic achievement and social adjustment among youth. However, links between school climate and brain structure have not been investigated to date. In this study, we investigated whether school climate was associated with executive function (EF) and brain structure (cortical thickness and surface area) in children and adolescents. We further examined whether these links varied as a function of socioeconomic background. Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 103 publications
(151 reference statements)
3
21
0
3
Order By: Relevance
“…A similar example can be found in considering the role of violence in children's lives as costly to their EF and self‐regulation. Our analyses as well as those of our colleagues (Heissel, Sharkey, Torrats‐Espinosa, Grant, & Adam, ; McCoy, Raver, & Sharkey, ; Piccolo, Merz, & Noble, ; Raver et al, ; Sharkey, Tirado‐Strayer, Papachristos, & Raver, ) have convincingly demonstrated that environmental threat, in the forms of gun violence and lack of school safety, has clearly deleterious consequences for children's opportunities for learning, given that exposure to both acute and chronic threat disrupts children's attention and self‐regulation. A new generation of scholars is pressing our field to more actively name the structural inequalities regarding who enacts threatening behaviour versus who is exposed to threat, where, and when.…”
Section: How We Frame the Problem: Expanding Our Modelssupporting
confidence: 70%
See 1 more Smart Citation
“…A similar example can be found in considering the role of violence in children's lives as costly to their EF and self‐regulation. Our analyses as well as those of our colleagues (Heissel, Sharkey, Torrats‐Espinosa, Grant, & Adam, ; McCoy, Raver, & Sharkey, ; Piccolo, Merz, & Noble, ; Raver et al, ; Sharkey, Tirado‐Strayer, Papachristos, & Raver, ) have convincingly demonstrated that environmental threat, in the forms of gun violence and lack of school safety, has clearly deleterious consequences for children's opportunities for learning, given that exposure to both acute and chronic threat disrupts children's attention and self‐regulation. A new generation of scholars is pressing our field to more actively name the structural inequalities regarding who enacts threatening behaviour versus who is exposed to threat, where, and when.…”
Section: How We Frame the Problem: Expanding Our Modelssupporting
confidence: 70%
“…See, for example, recent calls for the science of self‐regulation and EF to be used to reduce harsh, “no excuses” practices of social exclusion in schools serving students of colour (Bailey, Stickle, et al, ). Several new studies suggest the benefits of positive academic and emotional support for students' EF in school settings, with evidence accruing on the role of school climate through both behavioural and neurobiological levels (Piccolo, Merz, & Noble, ). Our field increasingly recognizes students themselves as active interpreters of their own experiences of inequality and as agents in shaping change (Godfrey & Cherng, ; Roy, Raver, Masucci, & DeJoseph, ), including through programs of restorative justice in fostering positive classroom and school climate.…”
Section: New Directions For Research On Ef: With Whom and For Whom Armentioning
confidence: 99%
“…While null effects of caregiving on cortical thickness have also been reported ( Avants et al, 2015 ; Leblanc et al, 2017 ), accumulating evidence highlights the importance of the caregiver/child relationship and demonstrates that both positive and negative caregiving experiences impact structural brain development ( Deane et al, 2020 ). Factors such as greater neighborhood disadvantage ( Whittle et al, 2017 ) and positive school environments ( Piccolo et al, 2019 ) have also been independently associated with increases in cortical thickness during development. However, less is known about the ways in which neighborhood and school contexts may interact with other environmental factors to influence brain structure.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, executive function reflects structure and functional aspects of the brain cortex and white matter [ 44 , 53 , 54 ]. To give examples, executive function is linked to cortical thickness [ 41 , 55 ], cortical function [ 53 ], white matter structure and volume [ 44 , 53 , 54 ], and functional connectivity between various brain regions, and cortex [ 42 ].…”
Section: Introductionmentioning
confidence: 99%